Effects of valproic acid on histone deacetylase inhibition in vitro and in glioblastoma patient samples. Issue 1 (12th November 2019) - Berendsen, Sharon; Frijlink, Elselien; Kroonen, Jèrôme; Spliet, Wim G M; van Hecke, Wim; Seute, Tatjana; Snijders, Tom J; Robe, Pierre A
Abstract: Background: The antiepileptic drug valproic acid (VPA) inhibits histone deacetylase in glioblastoma cells in vitro, which influences several oncogenic pathways and decreases glioma cell proliferation. The clinical relevance of these observations remains unclear, as VPA does not seem to affect glioblastoma patient survival. In this study, we analyzed whether the in vitro effects of VPA treatment on histone acetylation are also observed in tumor tissues of glioblastoma patients. Methods: The in vitro effects of VPA treatment on histone acetylation were assessed with immunofluorescence and western blotting. On tissue microarrays and in fresh-frozen glioblastoma tissues we investigated the histone acetylation patterns of patients who were either treated with VPA or did not receive antiepileptic drugs at the time of their surgery. We also performed mRNA expression-based and gene set enrichment analyses on these tissues. Results: VPA increased the expression levels of acetylated histones H3 and H4 in vitro, in agreement with previous reports. In tumor samples obtained from glioblastoma patients, however, VPA treatment affected neither gene (set) expression nor histone acetylation. Conclusions: The in vitro effects of VPA on histone acetylation status in glioblastoma cells could not be confirmed in clinical tumor samples of glioblastoma patients using antiepileptic doses of VPA, which reflects the lack of effect of VPA on the clinical outcome of glioblastoma patients.